Taxonomic significance of stomatal complex in fifteen species of Dendrobium Swartz (Orchidaceae) of Nepal - Pradhan, Baba Maiya; Bajracharya, Devendra M. (Journal of Natural History Museum, 2018)
Dendrobium Swartz is one of the largest and most problematic genus of the tribe Dendrobieae of the family Orchidaceae. Nepal harbors about thirty-one species of Dendrobium. Micro morphological characters like the stomatal complex in fifteen species of DendrobiumSwartz (Orchidaceae) of Nepal were studied for understanding the taxonomic significance of stomatal complex within the genus. For the study of stomatal complex of leaf, Carpenter’smethod was followed. Stomatal index and stomatal frequency were calculated using formulagiven by Salisbury. The terminologies used for the stomatal complex type were followed those of Patel. In all species the leaf surface was found hypostamic. Tetracytic (a-tetra-monocyclic,b-tetra-monocyclic and c-tetra-monocyclic) and eupara twi-monocyclic with hexa-monocyclictypes of stomata were recorded in the genus. Tetracytic type was found in fourteen species and eupara twi-monocyclic with hexa-monocyclic was found in only one species. The elliptical shape of stomata was found in more species than the circular shape. The epidermal cells of leaf was found rectangular, square, polygonal to irregular. The distribution of stomata on leaf surface, type of stomata and shape of epidermal cells were found to be taxonomically significant. These characters could be used as distinguishing characters to delimit the species in the genus.